2014
DOI: 10.1016/j.cattod.2013.12.037
|View full text |Cite|
|
Sign up to set email alerts
|

NOx storage and reduction pathways on zirconia and titania functionalized binary and ternary oxides as NOx storage and reduction (NSR) systems

Abstract: a b s t r a c tBinary and ternary oxide materials, ZrO 2 /TiO 2 (ZT) and Al 2 O 3 /ZrO 2 /TiO 2 (AZT), as well as their Ptfunctionalized counterparts were synthesized and characterized via XRD, Raman spectroscopy, BET, in situ FTIR and TPD techniques. In the ZT system, a strong interaction between TiO 2 and ZrO 2 domains at high temperatures (>973 K) resulted in the formation of a low specific surface area (i.e. 26 m 2 /g at 973 K) ZT material containing a highly ordered crystalline ZrTiO 4 phase. Incorporatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Detailed information regarding the synthesis procedures of Al 2 O 3 /ZrO 2 /TiO 2 (AZT, Al 2 O 3 : ZrO 2 : TiO 2 = 50 : 35 : 15, by mass) can be found in one of our recent reports. 18 The Pt/AZT material was prepared via a wetness impregnation method utilizing PtIJNH 3 ) 2 IJNO 2 ) 2 (Aldrich, diamminedinitritoplatinumIJII), 3.4 wt% solution in dilute NH 3 IJaq)). Before the incorporation of 1 wt% Pt, the Al 2 O 3 /ZrO 2 /TiO 2 support material was initially calcined in air at 973 K for 150 min in order to remove carbonaceous species and organic precursors.…”
Section: Materials Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…Detailed information regarding the synthesis procedures of Al 2 O 3 /ZrO 2 /TiO 2 (AZT, Al 2 O 3 : ZrO 2 : TiO 2 = 50 : 35 : 15, by mass) can be found in one of our recent reports. 18 The Pt/AZT material was prepared via a wetness impregnation method utilizing PtIJNH 3 ) 2 IJNO 2 ) 2 (Aldrich, diamminedinitritoplatinumIJII), 3.4 wt% solution in dilute NH 3 IJaq)). Before the incorporation of 1 wt% Pt, the Al 2 O 3 /ZrO 2 /TiO 2 support material was initially calcined in air at 973 K for 150 min in order to remove carbonaceous species and organic precursors.…”
Section: Materials Synthesismentioning
confidence: 99%
“…Along these lines, in our former studies we have focused on the design, synthesis and characterization of a variety of binary and ternary mixed metal oxide systems which are promoted with reducible oxides such as Fe 2 O 3 /Fe 3 O 4 , 12 TiO 2 , 9,[13][14][15][16] CeO 2 , 8,17 and ZrO 2 . 18 For instance, we have demonstrated that CeO 2 is an effective promoter enabling a significant improvement in the NO x reduction and sulfur regeneration of NSR/LNT catalysts. 8,17 On the other hand, while TiO 2 promotion facilitates the sulfur release from a poisoned NSR/LNT catalyst, 9,16 due to the strong interaction between TiO 2 and BaO domains, BaO can diffuse into TiO 2 , forming complex mixed oxides leading to thermal aging and deactivation.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Lean burn engines have become very popular in recent years as they offer high fuel efficiencies and lower CO 2 emission. NO x storage and reduction (NSR) catalytic technology is one of the most popular solutions for lean-NO x aftertreatment applications [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. NO oxidation/reduction ability and resilience against sulfur/phosphorous [13,15,19,20] are among the most vital capabilities that are essential for such NO x abatement (i.e.…”
Section: Introductionmentioning
confidence: 99%